2016
DOI: 10.1103/physreve.94.022142
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and scaling properties of nonequilibrium fluctuations in liquid mixtures

Abstract: Diffusion in liquids is accompanied by nonequilibrium concentration fluctuations spanning all the length scales comprised between the microscopic scale a and the macroscopic size of the system, L. Up to now, theoretical and experimental investigations of nonequilibrium fluctuations have focused mostly on determining their mean-square amplitude as a function of the wave vector. In this work, we investigate the local properties of nonequilibrium fluctuations arising during a stationary diffusion process occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…As in any linearized model, the key assumption is that fluctuations represent small perturbations of the macroscopic variables. This assumption is confirmed by experiments and simulations, even under microgravity conditions where the amplitude of the fluctuations is not damped by external forces [12,13,[18][19][20]. Notwithstanding the effectiveness of linearized hydrodynamics, recent theoretical work has found that the cumulative contribution of secondorder terms to the equations is far from being negligible.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…As in any linearized model, the key assumption is that fluctuations represent small perturbations of the macroscopic variables. This assumption is confirmed by experiments and simulations, even under microgravity conditions where the amplitude of the fluctuations is not damped by external forces [12,13,[18][19][20]. Notwithstanding the effectiveness of linearized hydrodynamics, recent theoretical work has found that the cumulative contribution of secondorder terms to the equations is far from being negligible.…”
Section: Introductionmentioning
confidence: 61%
“…The procedure is similar to that followed in the three-dimensional case [19]. The calculation requires the introduction of a small-wavelength cutoff Q.…”
Section: Root-mean-square Amplitude Of Fluctuationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, theory and experiments refer only to ideal conditions as for example stationary states, small gradients, and diluted systems. In recent years a number of theories [23][24][25][26][27][28] and some preliminary experiments [29][30][31] have indicated the importance of a deeper understanding of NEFs in more general cases.…”
Section: Introductionmentioning
confidence: 99%